From dermatological conditions to COVID‐19: Reasoning for anticoagulation, suppression of inflammation, and hyperbaric oxygen therapy. Issue 1 (30th November 2020) - Criado, Paulo Ricardo; Miot, Hélio Amante; Pincelli, Thais Prota Hussein; Fabro, Alexandre Todorovic
Abstract: COVID‐19 generates a complex systemic inflammatory response that can lead to death due to wide macrophage activation, endothelial damage, and coagulation in critically ill patients. SARS‐CoV‐2‐induced lung injury due to inflammatory mediated thrombosis could be similar to the livedoid vasculopathy in the skin, supporting a translational comparison of these clinical settings. In this article, we discuss anticoagulation, suppression of inflammatory response, and hyperbaric oxygen therapy in the context of severe COVID‐19 and livedoid vasculopathy.